Pengaruh L14 terhadap Peningkatan Kontraksi pada Kala I Persalinan - Lathifah, Neneng Siti; Iqmy, Ledy Octaviani (Politeknik Kesehatan Tanjungkarang, 2018)
The old partus is one of the causes of maternal death. Based on the date The Renstra of Provincial Health Office (2015) found that the old average partus in the world caused maternal mortality by 8%, in Indonesia by 9% and in Lampung province by 0,63%. The purpose of this study is to determine the effect of L14 against increasing contraction in the first stages labor mother in BPM Lia Maria Bandar Lampung Regency 2018. This type of research uses quantitative research with quasy experiment. The population in this study were all patients inpartu in the first stages labor mother at BPM Lia Maria Bandar Lampung 2018. Amounted to 83 people. Samples to 42 people. Technic Sampling Purposive Sampling With sample criteria divided into two, namely inclusion and exclusion. The data collection tool used in this research is to fill in the observation sheet and fill partograph. The statistical test used is T-Test. Statistical test results obtained p-value 0.000<0.05. For practice land or BPM can be used as a solution that massage at the L14 point given to the mother in part at the active phase affects the increase in contraction, so that it can speed up the labor process and without harmful side effects.